Ecological Preventive Empathy: A Proposal for Ethical Articulation in Times of the Antropocene; [Empatía Preventiva Ecológica: Propuesta Para la Articulación Ética en Tiempos del Antropoceno] - Bamaca-Lopez, E (Centro Universitario de Anapolis, 2024)
The deplorable state of the environment in this second decade of the 20th century invites us to reassess the ethical outlooks and approaches carried out on the relationship of the human being and his environment. Thus, the need for a principle of incidence that articulates human action on the environment is evident: the ecological preventive empathy. The present text develops this proposal through a reflective journey on the needs and characteristics of this new geological epoch, the Anthropocene, where the human being is positioned as a force of impact for his environment. Here we analyse how ethical approaches have failed by presenting a normative disjunction, generalizing proposals that are not applied in singular cases, and denoting the ethical urgency of new solutions. The reflective advances of recent years and the new theoretical approaches to the relationship of the human being with the environment have presented a new environmental philosophy with postulates such as Deep Ecology and Ecosophy. Based on these new ideas, the ecological preventive empathy proposal is built. In this text, the different meanings of the elements that constitute this idea, its scope of application, and its moral importance will be addressed. It is concluded how this new proposal constitutes an overcoming of the problematizations of the normative disjunction and a way to achieve an efficient ecological ethics. © 2024 Centro Universitario de Anapolis. All rights reserved.